Measurement of renal function using perfusion study by multi detector computed tomography - Mohamad, Mohaslinda (2011)
INTRODUCTION Renal function is an indication of the state of the kidney and its role in renal physiology. Accurate measurement of total or differential renal function plays an important role in the clinical management of various renal diseases. The Glomerular filtration rate (GFR) has been shown to be a reliable index to physiologic renal function (Shannon JA et al). Tissue perfusion can be estimated by calculating time – attenuation curve from dynamic CT acquisitions also known as CT perfusion (CTP) study (K A Miles et al., 1991). Currently, Perfusion CT has also been applied in a range of additional clinical areas. This study investigates the perfusion parameters in evaluation of the renal function using MDCT. OBJECTIVE This study aims to evaluate the renal perfusion and to compare with estimated glomerular filtration rate (eGFR) by using multi detector computed tomography. MATERIAL AND METHOD Thirty two patients who fulfilled the inclusion criterias were enrolled in this study which was carried out from November 2009 till October 2010, in Department of Radiology, Hospital Universiti Sains Malaysia. Blood for plasma renal function test which includes the urea and creatinine was taken prior to the CT examination. All the subjects underwent plain CT scanning of the abdomen using a 64-multidetector CT SIEMENS SOMATOM Definition AS followed by perfusion scanning done at the level of renal hilum. All images were transferred to a SIEMENS SOMATOM Definition AS workstation analysis. The data was analyze using time-density curve. The cursor was set on the aorta at the renal hilum level. The region of interest (ROI) was located at the cortex, medulla and whole kidney, away from the vessels. The average tissue attenuation using a manually drawn ROI on each image was automatically calculated and perfusions parameters which include blood flow (BF), blood volume (BV), mean transit time (MTT), time to peak (TTP) and maximal intensity phase (MIP) value were measured. Pearson product – moment correlation coefficients were calculated to assess relationship between the BF, BV, MTT, TTP as well as MIP with eGFR. RESULT Pearson analysis revealed the significant inverse correlation between eGFR and TTP in cortex, medulla and whole kidney bilaterally (p<0.05). However, there is no significant correlation found between BF, BV, MTT and MIP with eGFR (p>0.05). CONCLUSION This study showed that time to peak (TTP) is a potential parameter to estimate the GFR, and multidetector computed tomography (MDCT) is a useful tool in estimating the regional renal function in non invasive way.